Impact of Digital Shariah Banking Systems on Cash-Waqf amongst Muslim Millennials - Hafidhotul Amaliyah; Djoko Hartono (Budapest International Research and Critics University, 2022)
This study has two objectives, the first is to explore the variables that affect the intention to pay cash waqf online and the second is to investigate the moderating effect of experience on the variables that affect the intention to pay cash waqf online using mobile learning of Indonesian Islamic banks in Indonesia millennials in Surabaya. This study uses a quantitative approach, using a questionnaire survey on Muslim millennials in six big cities in Indonesia to collect the required data from the target group using purposive sampling method, and then the data is analyzed using the Structural Equation Modeling-analysis technique. Partial Least Square (PLS-SEM) with the help of SmartPLS. This study is one of the first studies to investigate the factors that influence online cash waqf donations among millennial Muslims in Surabaya using UTAUT theory.